Fabrikasi Profil Siku Baja Penyangga Rak Dinding Ukuran 150x150x0,5mm, Kapasitas 40 Biji/Jam (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The weak and less rigid profile of the shelf support elbow on the supporting wall with dimensions of the two elbows 15 cm long, 3.5 cm wide, 0.5 mm thick from low carbon steel is the problem faced. The purpose of fabrication is to obtain a shelf support elbow profile with dimensions of the two elbows 15 cm long, 3.5 cm wide, 0.5 mm thick from low carbon steel that is strong and stiff enough. The manufacturing method includes: design of the shelf support elbow profile, selection of 0.5 mm thick plate from low carbon steel, precision cutting (shearing) measuring 30 cm long, 3.5 cm wide, bending at a 90o angle with a V-die press brake machine, forming a 3 mm radius reinforcing groove for the 90o angle, drilling 6 holes with a diameter of 3.5 mm, finishing and painting, and quality and dimension inspection. The fabrication results are in the form of a shelf support angle profile on a supporting wall with dimensions of 15 cm in length for both angles, 3.5 cm in width, 0.5 mm in thickness from low carbon steel that can withstand a load of 2 kg, a total production cost of IDR 14,000/unit, a production process duration of 1.5 minutes/unit which implies that the shelf support angle profile is able to withstand vertical loads with 3 steel screws with a diameter of 3 mm x 35 mm.